Prostaglandin E 2 -EP2/EP4 signaling induces the tumor-infiltrating Treg phenotype for tumor growth - Ryuma Matsuura; Siwakorn Punyawatthananukool; Ryoji Kawakami; Norihisa Mikami; Shimon Sakaguchi; Shuh Narumiya (Proceedings of the National Academy of Sciences, 2025)
Foxp3 + regulatory T cells (Tregs) heavily infiltrate malignant tumors and restrict antitumor immunity. These tumor-infiltrating Tregs (TI-Tregs) adopt a distinct phenotype by expressing a unique set of genes. This TI-Treg gene expression signature is conserved in TI-Tregs across species and tumor types and stages, suggesting the presence of a common inducing mechanism in the tumor microenvironment (TME). However, identity of such a mechanism remains elusive. Here, we show that prostaglandin E 2 (PGE 2 ) produced in TME directly acts on its receptor EP2/EP4 on Tregs to induce the TI-Treg phenotype. PGE 2 added to TCR-activated Tregs induces a set of genes, many of which are included in the TI-Treg signature, in both induced Tregs (iTregs) and naturally occurring Tregs (nTregs) via EP2/EP4- cAMP-PKA pathway. Concomitantly, PGE 2 -treated Tregs exhibit potent suppressive activity to CD8 + T cells and strongly inhibit their proliferation in an EP4 dependent manner. Consistently, selective loss of EP2 and EP4 in mouse Tregs reduces expression of those genes in Tregs infiltrating Lewis lung carcinoma 1 (LLC1) mouse tumor and significantly delays the tumor progression. In human FOXP3 + iTregs, PGE 2 -EP4 signaling upregulated the expression of Treg signature genes, FOXP3, CD25, and CTLA-4 as well as a typical TI-Treg signature gene, 4-1BB, and enhanced suppressive activity. Furthermore, analysis of single-cell RNA sequencing of nasopharyngeal cancer patients demonstrates preferential expression of the TI-Treg signature genes in Tregs infiltrating the PTGS2 hi tumor group compared to the PTGS2 lo tumor group. These findings suggest that PGE 2 -EP2/EP4 signaling is one of the core mechanisms inducing the TI-Treg phenotype in TME for tumor growth.